Coronary stent-graft use to salvage a juxta-anastomotic arterial rupture complicating a case of radio-cephalic fistuloplasty - Zhiyuan Lin; Neha Kallam; Ruhaid Khurram; Ammar Al Midani; Mohamed Khalifa (CVIR Endovascular, 2022)
Abstract Background Stenosis is a common complication of haemodialysis arteriovenous accesses. Endovascular approaches with percutaneous transluminal fistuloplasty have largely replaced open surgical approaches as first line treatment. Vessel rupture is an uncommon complication of fistuloplasty and most reports describe venous rupture. Stent-graft deployment can salvage this, however, its use requires careful assessment of the distal vasculature. Arterial rupture with fistuloplasty has rarely been described in the literature. This is a novel case describing the use of a BeGraft coronary stent-graft to manage juxta-anastomotic arterial rupture and pseudoaneurysm complicating fistuloplasty. Case presentation A 77 year old female with end stage renal failure secondary to systemic amyloid light chain type amyloidosis was referred for a suspected radio-cephalic arteriovenous fistula stenosis after difficulty cannulating with poor flow during dialysis and clinical reduction in the fistula thrill. Both Doppler ultrasound and intravenous fistulography confirmed a venous stenosis 2 cm distal to the anastomosis. The stenosis was treated by fistuloplasty, however, this was complicated by a rupture of the juxta-anastomotic arterial segment intraoperatively. Intermittent balloon tamponade was used to minimise extravasation although a pseudoaneurysm formed within the damaged arterial segment. The patient’s distal neurovascular status was assessed using the Barbeau test and we sonographically confirmed adequate retrograde arterial flow via a complete palmar arch directing blood from the ulnar artery. After discussion with the renal transplant team, a 4 mm BeGraft coronary stent-graft was deployed to control haemorrhage and bypass the pseudoaneurysm until adequate haemostasis and fistula flow was achieved. Follow-up 3 months post-procedure reported the patient continued with haemodialysis using the stented fistula with no further complications. Conclusions To our knowledge, this is the first case report describing the application of BeGraft coronary stent-grafts to salvage fistuloplasty of a radio-cephalic arteriovenous fistula stenosis complicated by juxta-anastomotic arterial rupture and pseudoaneurysm formation. We demonstrate the safety and short-term efficacy of this technology.